Akulturasi Budaya dalam Ritual Pemamanan: Tradisi dan Identitas Masyarakat Alas di Aceh Tenggara - Mulya, Riska; Rohani, Laila; Naldo, Jufri (Local History & Heritage, 2025)
This study examines the Pemamanan tradition, which is the cultural heritage of the Alas tribe in Kelapa Gading Village, Southeast Aceh Regency. Pemamanan is a traditional ritual in which the uncle (maternal brother) is fully responsible for financing various traditional events for his nephews. This study aims to reveal the implementation process, traditional expressions, and series of activities in the Pemamanan tradition. Using a qualitative method and descriptive approach, this study combines a literature review from related journals and research with an empirical approach through interviews, observations, and documentation. The results show that the Pemamanan tradition includes various traditional events with the same name, where the implementation process varies depending on the type of event. In the context of marriage, this tradition includes a series of rituals from Ngentat Ken Tebekhas to the Njagai event at night. This research also reveals the dynamics in the implementation of traditions, including debates about the number of gifts to nephews and the scale of events, both simple and large-scale.